TINJAUAN YURIDIS MENGENAI PENGANGKATAN PENYELIDIK DAN PENYIDIK PADA KOMISI PEMBERANTASAN KORUPSI (STUDI KASUS PUTUSAN PRA PERADILAN NOMOR 36/Pid.Prap/2015/PN.Jkt.Sel) - SIRINGORINGO, JASTIN MIKSONDES; ', Erdianto; ', Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
One of the new legal institutions created in the book of the law of criminal procedure is the Pretrial, then from that point on, the exsistence of chaotic appointment about some investigating officer in police of Republic of Indonesia by the Corruption Eradication Commission which becomes a prolonged polemic for the agencies concerned and the investigating officer’s appointment were not from police institution. Within the case Hadi Poernomo as the petitioner submit pretrial petition towards the appointment onsidered contrary the point because is not present in the code of criminal procedure which is detrimental for him towards investigation and investigating officer that have been carried out. The purpose of the writing of this scription is to know: First, investigation and investigation officer‘s appointment in pretrial petition Number 36/Pid.Prap/2015/PN.Jkt.Sel. Second, the appointment process of investigation and investigating officer in corruption eradication commision in case Number 36/Pid.Prap/2015/PN.Jkt.Sel already appropriate in prespective Integrated Criminal Justice System. Third, the legal consequences of the investigation and investigating officer‘s appointment in corruption eradication commision in pretrial petition Number 36/Pid.Prap/2015/PN.Jkt.Sel.This research used kind of normative because reviewing pretrial petition by Hadi Poernomo in case Number 36/Pid.Prap/2015/PN.Jkt.Sel that include the approach to cases, legislation and conceptual. Technique for collecting and processing of legal materials in the writing of this scription is to collect legal materials of primary and secondary legal materials, which are then carried out an inventory and analysis of both the primary legal materials nor secondary law materialsBased on the result, there are three main things that can be concluded. First, based on the code of criminal procedure valid until nowdays calrify that Corruption Eradication commision does not have authory to make appointment about the investigation and investigating officer who did not come from the institution Indonesian National Police and the Attorney General of the Republic of Indonesia. Second,according to the perspective of the Integrated Criminal Justice System, the authority of the Corruption Eradication Commision to conduct the appointment of investigation and investigating officer in the case Number 36/ Pid.Prap/2015/ PN.Jkt.Sel is not appropriate because according to the law it is a deviation from the provisions applicable for the on going Integrated Criminal Justice System. Third, the appointment of investigator and investigating officer at the Corruption Eradication Commission in case Number 36 / Pid.Prap / 2015 / PN.Jkt.Sel that deviate from the Code of Criminal Procedure Code and Law Number 30 Year 2002 on Eradication Commission Corruption itself, then the activities of inquiries and investigations that have been carried out is an activity that resulted in formal defect such activities become null and void.Keywords : Investigation – Investigating officer – Pretrial